Rethinking the structure of Islamic economics: the economic man imperative - Mohd Yusop, Mohd Mahyudi (2016)
The end of value-free economics presents a positive outlook for Islamic economics. Nonetheless, progress is only viable when this discipline has a solid scientific structure. Thus, this paper aims to highlight the economic man imperative in projecting Islamic economics as a normal science. This paper first explores Islamic economics’ current state of readiness to fulfill its promising future. Unfortunately, the authoritative view is that Islamic economics is not in proper order. Consequently, Arif’s (1985a and 1985b) Islamic economics scientific structure is utilized to locate that stage which requires serious improvement. At the basis of micro-foundation stage, the economic man imperative emerges out of this identification exercise. Thus, the most important implication here is the replacement of homo Islamicus with the concept of ‘universal man’ which proffers several advantages. Apart from the other stages in the structure, this ‘universal man’ needs immediate refinement to strengthen the edifice of Islamic economics science.